2021
DOI: 10.1002/aur.2644
|View full text |Cite
|
Sign up to set email alerts
|

Co‐occurring conditions and racial‐ethnic disparities: Medicaid enrolled adults on the autism spectrum

Abstract: Evidence suggests that autistic adults have higher odds of developing several co‐occurring conditions, but less is known about disparities by race and ethnicity in this population. Using 2008–2012 Medicaid Analytic eXtract (MAX) data, we (i) identify the prevalence of co‐occurring conditions among the population of autistic adult Medicaid beneficiaries compared to a matched sample of those without an autism spectrum disorder (ASD) diagnosis, (ii) conduct logistic regression to estimate odds ratios for these he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 66 publications
0
27
2
Order By: Relevance
“…Other notable aspects of the work not included in Table 1 capture issues of diversity and representation. Seven studies included an explicit focus on issues of equity based on race, ethnicity, gender, and income (Benevides et al, 2022; McGhee Hassrick et al, 2021; Roux et al, 2022; Schott et al, 2022a; Shattuck et al, 2020; Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022). One review article noted that under‐represented study participants included autistic individuals who were women, transgender, non‐White, low income, and those with intellectual disability or with minimal speaking communication (McGhee Hassrick et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other notable aspects of the work not included in Table 1 capture issues of diversity and representation. Seven studies included an explicit focus on issues of equity based on race, ethnicity, gender, and income (Benevides et al, 2022; McGhee Hassrick et al, 2021; Roux et al, 2022; Schott et al, 2022a; Shattuck et al, 2020; Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022). One review article noted that under‐represented study participants included autistic individuals who were women, transgender, non‐White, low income, and those with intellectual disability or with minimal speaking communication (McGhee Hassrick et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Across domains (health, mental health, employment, etc. ), access, service use and outcomes varied by race/ethnicity, income, gender, and by intersections of these factors with autism diagnosis (Benevides et al, 2022; McGhee Hassrick et al, 2021; Roux et al, 2022; Schott et al, 2022a; Shattuck et al, 2020; Song, Nonnemacher, Miller, Anderson, & Shea, 2022; Song, Salzer, Nonnemacher, Miller, & Shea, 2022). Both service delivery and policy to support vocational programming varied widely across states with an evident lack of state planning for addressing the service needs of this growing population (Roux et al, 2019; Roux, Anderson, Rast, et al, 2018; Roux, Rast, Nye‐Lengerman, et al, 2018; Roux, Rast, & Shattuck, 2018).…”
Section: Resultsmentioning
confidence: 99%
“… 19 However, our findings are somewhat consistent with two studies that identified racial/ethnic health disparities among autistic adults and adults with IDD more generally. 31 , 62 In Medicaid data, Black, Hispanic, and Asian/Pacific Islander autistic beneficiaries tended to be less frequently diagnosed with mental health conditions, with the exception of schizophrenia, and more frequently diagnosed with several medical conditions including hypertension and diabetes in comparison with White autistic counterparts. 62 …”
Section: Discussionmentioning
confidence: 99%
“… 31 , 62 In Medicaid data, Black, Hispanic, and Asian/Pacific Islander autistic beneficiaries tended to be less frequently diagnosed with mental health conditions, with the exception of schizophrenia, and more frequently diagnosed with several medical conditions including hypertension and diabetes in comparison with White autistic counterparts. 62 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation